Detecting organic vapors using a conductometric sensor prepared from Ardel®D-100 and graphite - Yazici, Ozlem; Moroglu, M. Reyhan; Cankurtaran, Husnu; Cankurtaran, Ozlem; Karaman, Ferdane (SPRINGER WIEN, 2008)
The composites of graphite with Ardel((R))D-100 which is a trademark of a polyester of bisphenol-A with terephthalic and isophthalic acid were used as a sensing material in a conductometric vapor sensor. The magnitudes of responses are increased in the order of benzene, isobutyl acetate, isoamyl acetate, ethyl benzene and chloro benzene. This suggests that Ardel((R))D-100 can be used as a sensing material for chlorobenzene, ethyl benzene and isoamyl acetate. On the other hand, specific retention volumes of the sensed vapors on Ardel((R))D-100 coated on graphite were determined by inverse gas chromatography at temperatures between 200 and 260 degrees C. The distribution coefficient, K, of the vapors between stationary and mobile phases in the column was obtained. It was revealed for the first time that the logarithm of K-s of the solvents varies almost linearly with their responses based on conductometric resistance of the sensing polymer composite. Subsequently, the study suggests that gas chromatographic retention data can be used in prediction of the conductometric responses of a polymeric sensor to vapors.
Keywords: polyester of bisphenol-A; Ardel((R))D-100; inverse gas chromatography; distribution coefficient; vapor sensor; INVERSE GAS-CHROMATOGRAPHY; THERMODYNAMICS; EQUATION; POLYMERS; STATE; Chemistry